Acceptability of coronavirus disease 2019 vaccination among Indian health-care professionals: A cross-sectional survey - Manpreet Arora; Charu Khurana; Pulin Saluja; Aparna Dave (Tzu Chi Medical Journal)
Objective: The epidemic of novel coronavirus disease 2019 (COVID-19) has led to the development of several vaccine candidates which has been progressing at an unprecedented rate. Health-care professionals are somewhere standing between their professional commitments and personal well-being, amid concerns about the safety and efficacy of the vaccine. The present survey was conducted to analyze their approach toward vaccination. Materials and Methods: An online questionnaire-based cross-sectional survey was conducted among 250 health-care professionals comprised of Medical, Dental, Ayurveda, Physiotherapy doctors, and nursing staff working at a tertiary care hospital in Gurugram city. A self-administered 10-item questionnaire in the Google document format was developed to assess their perception and attitude toward vaccination. The present survey was carried out for 2 months from November to December 2020. The responses recorded were subjected to the statistical analysis using the Chi-square test and the level of statistical significance was set at P ≤ 0.05. Results: Among all participants, 72 (28.8%) were male and 178 (72.2%) were female. Of all, 60.4% of the health-care professionals somewhat or completely agreed to accept a vaccine as soon as it is available. Nursing staff reported more likely to accept COVID-19 vaccination than the other health-care professionals. Majority of the HPs (44%) were found to be concerned about the rapidity in the development of vaccine. Conclusion: The overall attitude toward vaccination was positive but specific concerns regarding COVID-19 vaccine are prevalent. Thus, to maintain the benefits of vaccination programs and for its successful implementation, understanding and addressing their vaccine hesitancy will be crucial.